Peningkatan Profesionalitas Guru IPA melalui Pelatihan Pengembangan Instrumen Assessment Kemampuan Metakognitif Berbantuan Media ICT - Wiono, Wisnu Juli; Yolida, Berti (Universitas Islam Negeri Raden Intan Lampung, 2021)
Education in 21st century is directed to prepare a generation of learners, problem solvers and have the ability to think critically and creatively. Classroom learning is designed to facilitate students in achieving these goals by providing metacognitive-oriented exercises. Utilization of information and communication technology in learning has a significant influence on student learning outcomes. The ability to compose test instruments that are oriented to high-level thinking and mastery of technological literacy are skills that must be possessed by teachers, especially during the COVID-19 pandemic. In fact, junior high school science teachers in East Lampung generally use test instruments from printed books and rely heavily on short message services (SMS) or Whatsapp in conducting learning. In these conditions, it is necessary to seek the right solution so that there is no loss of meaning in learning. The service activity began with a seminar on the nature of assessment, the use of ICT in learning, and the practice of compiling metacognition-oriented test instruments. At the end of the activity, participants were asked to present their work in front of the class in order to receive criticism and input from other participants and lecturers. The results of the service activities show that the understanding and ability of science teachers in East Lampung has increased. This can be seen from the instrument products produced that have met the standards in the assessment. This increase can be seen from the results of the n-gain analysis which is in the medium category.